Gypsum blocks produced from TiO2 production by-products. Issue 9 (2nd May 2016) - Zhang, Yihe; Wang, Fan; Huang, Hongwei; Guo, Yuxi; Li, Baoying; Liu, Yangyang; Chu, Paul K.
ABSTRACT: Calcined titanium gypsum was investigated by the ways of XRD (powder X-ray diffraction), XRF (X-ray fluorescence) and TG-DTA (thermogravimetric–differential thermal analyses). It was employed as raw material for making lightweight materials. The influence of cement, amount of water/solid (W/S) ratio, water-reducing agent, citric acid content and the hydration age on the gypsum blocks was investigated. The results showed that the optimum W/S ratio, cement content and water-reducing agent are 0.9, 10% and 2 wt% for the calcined gypsum from titanium gypsum, respectively. The 5.96 MPa was attained after 7 days of ageing. It was also found that the citric acid is inappropriate to be used in the production of gypsum blocks from TiO2 production by-products.